ILLUMINATI SYMBOL REPRESENTATION IN DESIGN SHIRT AYE! DENIM - Rona Rizka; Tantri Puspita Yazid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The development of the fashion world are growing rapidly and creatively to make the fashion business activists have to create something different from the others. Designs on fashion products to convey a hidden message for the user as well as the look of the design. Aye! One fashion denim brand in Indonesia to bring the design of its products with the theme Secret Society, the Illuminati, and Freemasonry. This study aims to look at how the meaning and ideology of Illuminati on t-shirt design that was released by Aye! Denim.This study uses qualitative descriptive study, with the selection of informants using purposive sampling theory, the author chose some informants who have a relationship with Aye! Denim, the Owner of Aye! Denim, and users of the product from Aye! Denim. Data collection techniques in this research with in-depth interviews, observation, and documentation. For data analysis techniques, using three stages of Roland Barthes significance. The first phase, peeling connotations, the second phase of search for meaning denotation, and the third phase concluded myths and ideologies contained in t-shirt design Aye! Denim.The results of this study indicate that the meaning and ideology embodied in the design Aye! Denim contains about the existence of a huge plan designed by the Secret Society, the Illuminati, and Freemasonry. The agenda is driven by the people behind the scenes who infiltrated through the administration of a country. The purpose of the agenda is to create a new world government or commonly called the